'Talking a different language': a qualitative study of chronic low back pain patients' interpretation of the language used by student osteopaths. (June 2017) - Thomson, Oliver P.; Collyer, Katie
Abstract: Background: A growing body of research evidence has identified psychosocial factors to be important in the management of low back pain (LBP). Evidence suggests that healthcare professionals have a considerable influence on patients' attitudes and beliefs. Few studies have investigated how patients experiencing LBP interpret the language used by their osteopath during their consultation and the impact of language on their attitudes and beliefs of their LBP. Objectives: To explore and describe how patients with acute or chronic LBP interpret the language used by student osteopaths when explaining their diagnosis, and the impact their interpretation has on their attitudes and beliefs of their LBP. Method: Semi-structured qualitative interviews were conducted with a purposive sample of nine patients experiencing LBP who had recently attended an osteopathic teaching clinic in the UK. Interviews were transcribed verbatim and elements of grounded theory were used as a framework for data analysis. Results: Participants expressed a range of interpretations in response to the language used when discussing their LBP. The use of medical words, metaphors and analogies, reassurance and the patient-practitioner relationship were identified as factors influencing the level to which participants engaged, taking an active role in their care. Conclusions: The language used by student osteopaths' influences patient beliefs about LBP in a variety of ways. The current study furthers understanding of how language contributes to these beliefs, identifying ways through which communication can contribute to improved healthcare through enhancing patient engagement.